2-D prediction method for multi-row film cooling effectiveness. (25th November 2021) - Chen, Ziyu; Mao, Yinbo; Hu, Kexin; Su, Xinrong; Yuan, Xin
Abstract: This work develops a new and effective method to predict the 2-D cooling effectiveness distribution. The assumption in the existing 1-D method is abandoned and replaced by a scalar diffusion equation to model the lateral spreading of the coolant. The proposed model can be used for predicting 2-D multi-row cooling performance and is validated over four arrangements of double-row cooling holes against in-house experimental data. The paper further presents the advantages of the current method over the classic 1-D method. 2-D distributions for different multi-row configurations are successfully obtained and the relative error is reduced to 19.77% as opposed to that of 45.65% with the 1-D model. The time consumption by the proposed method is on the order of 1 × 1 0 − 3 s which is exceedingly efficient for the cooling design process. To sum up, the proposed method is accurate, capable of 2-D multi-row modeling and of simple form and high efficiency. Hence it is potentially an effective tool for film cooling design. Highlights: The 1-D method lacks the ability to differentiate cooling performance between multi-row arrangements. The proposed 2-D method demonstrates satisfactory accuracy in predicting multi-row cooling performance. The 2-D method is reliable in recognizing the local over-cooling or under-cooling. The relative error is reduced from 45.64% to 19.77% by adopting the 2-D method.